The Spanish Collocation Tool and Its Application in Corpus-Based Study of Spanish for Teaching and Learning - Lu 盧慧娟, Hui-Chuan; Song 宋采育, Cai-Yu; Cheng 鄭安中, An Chung (Círculo de Lingüística Aplicada a la Comunicación, 2021)
The purpose of this paper is to introduce a developed software program called the “Spanish Collocation Tool (SCT)” and its application in related corpus-based studies. The Spanish Collocation Tool (SCT) was designed to assist with the research and analysis of Spanish collocation. The SCT allows searches of collocated elements not limited to words, but also parts of speech and lemmas. Furthermore, it can compare two collocation lists to detect any significant differences between them. In this study, this collocation tool, SCT, and a constructed L3 Taiwanese learners’ written corpus of Spanish called CEATE were combined to create efficient access to results in a systematic approach. Furthermore, by using the SCT, the pedagogical implications of the search results for the development of on-line multimedia material for learning Spanish collocations are discussed in the end.